GENETIC DISORDER ALZHEIMER - Rani, Pratibha; Singh, Kamaldeep; Arjuna, Anania; Devi, Savita (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Alzheimer's disease (AD), slowly continuous neurological disorder, mostly appears in older >65 age that deals with the memory loss due to death or damage of brain cells and cognitive functions (thinking, reasoning, and behavior abnormalities) due to the accumulation of the specific protein (beta-amyloid protein) which form plaque and fibers (tau tangles) in the brain. Not only the genetic factors are responsible but also most of the non-genetic factors are responsible for AD. Several mutations in the gene (APP, APOE, PENS1, PENS2 on chromosome no. 21, 19, 14, 1) are responsible for causing four types of AD. Memory loss is most common sign of AD. Predisposing factors of AD are hereditary, severe brain injury or traumatic, and metabolic diseases such as diabetes mellitus, hypercholesteremia, and obesity. Although treatment can manage some symptoms in few people, but there is no current mechanism to cure AD or stop its progression. Beta-secretase inhibitor molecule prevents the first step in a chain accumulation which leads to the formation of amyloid plaque in the brain. However, the scientist or researchers have established a compound NIC5-15 they have been found NIC5-15 has safe and effectual treatment which has been used to stabilize cognitive performance in patients with mild to moderate AD.